Hormon Testosteron Dan Estadiol 17ß Dalam Plasma Darah Induk Betina Ikan Baung (Mystus Nemurus) - Kencana Putra, I Gede Deta; -, Wardiyanto; -, Tarsim (e-Jurnal Rekayasa dan Teknologi Budidaya Perairan, 2012)
The research about application of bovine testicular extract on female baung catfish (Mystus nemurus) was done for determining an optimum dosage and application periode of bovine testicular extract. The aim of this research is to increase testosteron and estradiol 17β concentration on blood as gonad developing hormone on female baung catfish broodstock. This  research used randomize blocked design with five treatments and three groups. Dosages of bovine testicular extract which used as treatment were 0; 0,75; 1,5; 2,5 and 4,5 mg/kg feed. The periodes of bovine testicular extract applied were 10; 20 and 30 days. This research used female baung catfish with average body weight of 400-500 g. This research done on July-September 2011 at Balai Benih Ikan Sentral (BBIS) Purbolinggo, East Lampung. Testosterone and estradiol 17β concentration was determined by Radioimmunoassay (RIA) technique at Indonesian Research Institute for Animal Production Ciawi, West Java. The result showed that the application of bovine testicular extract could increase testosteron and estradiol 17β concentration in blood plasma. Dosage 2.5 mg/kg feed could increase testosterone concentration on 278.91 ± 66.76 pg/ml and estradiol 17β concentration on 606.25 ± 187.97 pg/ml. The application periode of Bovine Testicular Extract for 30 days could  increase testosteron and estradiol 17β concentration on 254.38 ± 93.84 pg/ml and 514.55 ± 137.22 pg/ml.